Kwik kuts & co : Skinning machine / Mohammad Syahmi Nordin ... [et al] - Nordin, Mohammad Syahmi; Mhadrzir, Muhammad NadzirulRosli; Rosli, Aidil Fahmi; Rahmat, Muhammad Haziq Hasif; Muhammd Syzwan, Noor Aykin (2017)
This business plan is proposed to complete the assessment that was included in our subject which is Fundamentals of Entrepreneurship (ENT300). It is a five man company consisting of a General Manager, Administration Manager, Marketing Manager, Operational Manager, Financial Manager and a Chief Engineer. The business is amounted with RM100 000.00 budget. It is expected that our business will progress further and become more profitable in the long run. Our product also has more potential to be innovated in future. Kwik Kuts & Co is a company that dedicated to help people to reduce the time needed and man power for butcher to slaughter animals in Islamic way and effective. This compony can be categorized under the innovation and technology compony. The company's signature product is skinning machine : a portable machine that helps people reduce the time needed to skin animals